Experience on switching trientine formulations in Wilson disease: Efficacy and safety after initiation of TETA 4HCl as substitute for TETA 2HCl. Issue 2 (12th November 2022) - Mohr, Isabelle; Bourhis, Hélène; Woimant, France; Obadia, Mickael Alexandre; Morgil, Müzeyyen; Morvan, Erwan; Merle, Uta; Denk, Gerald; Poujois, Aurelia; Weiss, Karl Heinz
Abstract: Background and Aim: This retrospective, multicenter study aims to assess the efficacy and safety in Wilson disease (WD) patients treated with trientine tetrahydrochloride (TETA 4HCl) after switch from trientine dihydrochloride (TETA 2HCl). Methods: In total, 68 WD patients with stable copper metabolism were identified to receive TETA 4HCl (Cuprior™) after previous treatment with TETA 2HCl. We analyzed biochemical markers such as urinary copper, serum copper, non‐coeruloplasmin bound copper (NCC), and transaminases as well as clinical scores (APRI; FIB‐4 score) at baseline with a follow‐up (FU) of 12 months. Safety of TETA 4HCl treatment was based on reported adverse events (AEs). Results: The study cohort reflects a common WD cohort with a mean age of 20.3 years at diagnosis and 38.3 years at baseline. There are no significant differences concerning serum copper, NCC, transaminases, APRI, and FIB‐4 score in the 3‐month FU. Six‐month FU revealed a decreased AST ( P  = 0.008), APRI ( P  = 0.042), and FIB‐4 score ( P  = 0.039). GGT varied only borderline significantly in the 3‐month, but not in the 6‐month FU. Comparison of urinary copper within the subsets did not reveal a difference to baseline in all FUs, suggesting stable control of copper metabolism. Few AEs during TETA 4HCl treatment were reported, most commonly gastrointestinal discomfort. Only three treatments with TETA 4HCl were discontinued. Conclusion: Copper parameters and liver function were stable after treatment switch to TETA 4HCl. Treatment with TETA 4HCl was generally well tolerated. This study indicates that the switch from TETA 2HCl to TETA 4HCl is safe and viable.